[Cranfield DrivAer] CAD_Pack_8 Diffusers - Francisco Soares, Renan; Goñalons Olives, Sergio; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Diffusers CAD Pack (35% scaled-version), including:1. DrivAer_hp - Diffuser (side plates):Side plates used to generate an diffuser channel for slopping angles protruding the DrivAer main body (i.e. diffA < 7 deg).2. DrivAer_hp - Diffuser (diffA00 plain):Diffuser pack with a plain, sloping surface of 0 deg (i.e. 'no-diffuser' case).3. DrivAer_hp - Diffuser (diffA05 plain):Diffuser pack with a plain, sloping surface of 5 deg.4. DrivAer_hp - Diffuser (diffA10 plain):Diffuser pack with a plain, sloping surface of 10 deg.5. DrivAer_hp - Diffuser (diffA16 plain):Diffuser pack with a plain, sloping surface of 16 deg.6. DrivAer_hp - Diffuser (diffA05 SEP_on):Diffuser pack with a plain, sloping surface of 5 deg and 3 equidistant separators ('fins').7. DrivAer_hp - Diffuser (diffA10 SEP_on):Diffuser pack with a plain, sloping surface of 10 deg and 3 equidistant separators ('fins').8. DrivAer_hp - Diffuser (diffA16 SEP_on):Diffuser pack with a plain, sloping surface of 16 deg and 3 equidistant separators ('fins').CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(diffA) = nominal diffuser angle.(SEP_on) = use of longitudinal separators ('fins').-------------------------------------------------CAD designed and uploaded by:Renan F Soares - PhD in AerospaceApplied Aerodynamics GroupCranfield University, United Kingdom
Keywords: CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Diffuser'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'